Genetic analysis for yield and its attributes in safflower (Carthamus tinctorius L.): GENETIC ANALYSIS FOR YIELD AND ITS ATTRIBUTES IN SAFFLOWER - C MANIKYA MINNIE; S N C V L PUSHPAVALLI; K SUJATHA; S SANDEEP; C SUDHAKAR; T RAJESHWAR REDDY; C SUDHA RANI (Journal of Oilseeds Research, 2020)
The present investigation was carried out to study genetic variability, character association and genetic divergence for yield and its attributing traits among 70 genotypes of safflower at Agricultural Research Station, Tandur. The genotypic coefficients of variation (GCV) were less compared to the phenotypic coefficients of variation (PCV) for all the characters. High GCV was observed for seed yield/plot followed by test weight and high PCV values were observed for oil content, test weight, seed yield/plot and number of effective capitula/plant. High heritability coupled with high genetic advance was observed for seed yield/plot, number of seeds/capitulum, number of effective capitula/plant and days to maturity. Seed yield/plot was significantly and positively correlated with days to 50% flowering, days to maturity, number of seeds/capitulum and test weight. Path coefficient analysis indicated that days to maturity exhibited maximum direct effect followed by test weight and number of seeds/capitulum on seed yield. The genotypes were grouped into 11 different clusters based on Mahalanobis D2 statistics. Clusters VIII and IX exhibited maximum inter cluster distance. Seed yield/plot contributed most towards genetic divergence. Highest mean values were recorded for seed yield/plot in cluster IX, number of effective capitula/plant in Cluster X, number of seeds/ capitulum and test weight in Cluster XI.